Taxonomic Variability in the Electron Requirement for Carbon Fixation Across Marine Phytoplankton. Issue 1 (28th November 2020) - Hughes, David J.; Giannini, Fernanda C.; Ciotti, Aurea M.; Doblin, Martina A.; Ralph, Peter J.; Varkey, Deepa; Verma, Arjun; Suggett, David J.
Abstract : Fast Repetition Rate fluorometry (FRRf) has been increasingly used to measure marine primary productivity by oceanographers to understand how carbon (C) uptake patterns vary over space and time in the global ocean. As FRRf measures electron transport rates through photosystem II (ETRPSII ), a critical, but difficult to predict conversion factor termed the "electron requirement for carbon fixation" (Φe, C ) is needed to scale ETRPSII to C‐fixation rates. Recent studies have generally focused on understanding environmental regulation of Φe, C, while taxonomic control has been explored by only a handful of laboratory studies encompassing a limited diversity of phytoplankton species. We therefore assessed Φe, C for a wide range of marine phytoplankton ( n = 17 strains) spanning multiple taxonomic and size classes. Data mined from previous studies were further considered to determine whether Φe, C variability could be explained by taxonomy versus other phenotypic traits influencing growth and physiological performance (e.g., cell size). We found that Φe, C exhibited considerable variability ( 4–10 mol e ‐ · [mol C] −1 ) and was negatively correlated with growth rate ( R 2 = 0.7, P < 0.01). Diatoms exhibited a lower Φe, C compared to chlorophytes during steady‐state, nutrient‐replete growth. Inclusion of meta‐analysis data did not find significant relationships between Φe, C and class, or growth rate, although confounding factors inherent to methodological inconsistencies between studies likely contributed to this. Knowledge of empirical relationships between Φe, C and growth rate coupled with recent improvements in quantifying phytoplankton growth rates in situ, facilitate up‐scaling of FRRf campaigns to routinely derive Φe, C needed to assess ocean C‐cycling.